Imaging chromatin nanostructure with binding-activated localization microscopy based on DNA structure fluctuations - Szczurek, Aleksander; Mai, Sabine; Cremer, Christoph (Experimental eye research, 2017)
Abstract. Advanced light microscopy is an important tool for nanostructure analysis of chromatin. In this report we present a general concept for Single Molecu